The Effects of Cross-border M&As on the Acquirers' Domestic Performance – Firm-level Evidence - Joel Stiebale; Michaela Trax (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2010)
This paper provides empirical evidence on the effects of cross-border M&As on investing firms' domestic performance in the U.K. and France. We build a new firm-level dataset that combines a global M&A database with balance sheet data for the years 2000-2007. Combining matching techniques with a difference-in-differences estimator, we find that cross-border deals boost on average domestic employment, sales, and investment, and they are not accompanied by a downsizing of the domestic labor force in neither of both countries. Further, acquisitions in knowledge-intensive industries lead to improvements in domestic productivity. Our results display some heterogeneity across industries and types of acquisitions, suggesting a connection between the motives for international acquisitions and their resulting effects.
Keywords: F23; G34; L23; D24; 330; Multinational firms; cross-border M&A; productivity; employment growth; investment; Multinationales Unternehmen; Übernahme; Direktinvestition; Produktivität; Beschäftigungseffekt; Großbritannien; Frankreich